Preparation method of SEI membrane, lithium ion battery cell and lithium ion battery

By forming a multi-layer SEI film on the negative electrode of the lithium-ion cell, and adjusting the density of the SEI film using different additives and current conditions, the problem of large density impedance of the SEI film in the prior art is solved, and the circulation of the lithium-ion cell is improved Performance and battery life.

CN119181881APending Publication Date: 2024-12-24SHANDONG GEELY XINWANGDA POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310741166.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The SEI film prepared in the prior art is dense and has a large impedance, which is not conducive to the transmission of lithium ions, resulting in poor cycling performance of lithium ion cells.

Method used

Using the preparation method of multi-layer SEI film, by forming a multi-layer SEI film on the negative electrode of the lithium-ion cell, using different additives and current conditions for each liquid injection and decomposition, the density and structure of the SEI film are gradually adjusted, and the density and structure of the SEI film are approached from close to The electrodes are stacked outward to form an inner layer with good flexibility and a loose and porous outer layer, optimizing the performance of the SEI film.

Benefits of technology

It improves the cycling performance of lithium-ion cells, enhances the structural stability of the SEI film and the transmission capacity of lithium-ion, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181881A_ABST
    Figure CN119181881A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an SEI membrane, a lithium ion battery cell and a lithium ion battery, and relates to the technical field of lithium ion batteries. The method comprises the following steps: performing m times of liquid injection and m times of formation on a lithium ion battery cell so as to form a composite SEI film on a negative electrode; each time of formation comprises the following steps: carrying out constant-current charging to form a layer of SEI film on the negative electrode; the composite SEI film is formed by sequentially laminating m layers of SEI films formed by each time of formation; from the first liquid injection to the nth liquid injection, the used electrolyte contains an organic additive; from the (n + 1) th liquid injection to the mth liquid injection, the used electrolyte contains an inorganic additive; the densities of the m layers of SEI films which are sequentially stacked are gradually reduced from the direction close to the negative electrode to the direction far away from the negative electrode. The SEI membrane structure close to the negative electrode in the composite SEI membrane is good in stability, and the SEI membrane structure far away from the negative electrode is loose and porous, so that the transmission of lithium ions is facilitated, and the cycle performance of the lithium ion cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a SEI film, a lithium ion battery cell, and a lithium ion battery. Background Art

[0002] During the first charge and discharge process of lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material. This passivation layer is an interface layer with the characteristics of a solid electrolyte. It is an electronic insulator but an excellent conductor of lithium ions. Lithium ions can freely embed and escape through this passivation layer, so this passivation film is called a "solid electrolyte interface", or SEI film for short. The quality of the SEI film has a crucial impact on the performance of lithium-ion batteries.

[0003] In the prior art, when preparing the SEI film, in order to ensure the structural stability of the SEI film, a dense SEI film is usually prepared. However, using this prior art, the SEI film is dense and has a large impedance, which is not conducive to the transmission of lithium ions, resulting in poor cycle performance of lithium-ion batteries. Summary of the invention

[0004] The present invention provides a method for preparing an SEI film, a lithium ion battery cell and a lithium ion battery, aiming to solve the problem that the SEI film prepared in the prior art has a dense structure, but has good structural stability, but has a large impedance, which is not conducive to the transmission of lithium ions and causes poor cycle performance of the lithium ion battery cell.

[0005] A first aspect of the present invention provides a method for preparing a SEI film, comprising:

[0006] The lithium ion battery cell is injected with liquid m times and formed m times, and the formation is performed once after each injection, so as to form a composite SEI film on the negative electrode of the lithium ion battery cell; each injection includes: injecting electrolyte into the lithium ion battery cell; each formation includes: performing constant current charging on the lithium ion battery cell to form a layer of SEI film on the negative electrode of the lithium ion battery cell; the composite SEI film is formed by sequentially stacking m layers of SEI films formed by each SEI film formed by each formation; m is greater than or equal to 2, and m is a positive integer;

[0007] From the first injection to the nth injection, the electrolyte used contains an organic additive; from the n+1th injection to the mth injection, the electrolyte used contains an inorganic additive; n is greater than or equal to 1, and n is less than m; n is a positive integer;

[0008] From the first formation to the mth formation, the current of the constant current charging of each formation gradually increases; from the first formation to the mth formation, the temperature of each formation gradually increases; the temperature of each formation is less than or equal to 70° C.;

[0009] The density of the m layers of SEI films stacked sequentially decreases gradually from the negative electrode close to the lithium ion battery cell to the negative electrode far away from the lithium ion battery cell.

[0010] In the present invention, the composite SEI membrane is formed by stacking m layers of SEI membranes in sequence, each layer of SEI membrane formed by each formation; the structure or composition of the SEI membranes of different layers can be adjusted respectively, so as to facilitate obtaining a composite SEI membrane with better performance. From the first injection to the nth injection, the electrolyte used contains organic additives; from the n+1th injection to the mth injection, the electrolyte used contains inorganic additives; organic additives are conducive to preparing a SEI membrane with good flexibility. In the later charging and discharging process, the negative electrode of the lithium ion battery cell will expand and shrink, and the SEI membrane has good flexibility, is not easy to crack, and has good structural stability; inorganic additives are conducive to preparing a loose and porous SEI membrane, the SEI membrane is loose and porous, the impedance of the SEI membrane is small, which is conducive to the transmission of lithium ions in the SEI membrane, and also improves the rate performance of the lithium ion battery cell. When the current is small, the rate of forming the SEI film is slow, and it is easier to form a dense SEI film; when the current is large, the rate of forming the SEI film is fast, and it is easier to form a loose and porous SEI film. The current of the constant current charging of each formation gradually increases, which can make the density of the m layers of SEI film stacked in sequence from the negative electrode close to the lithium ion battery cell to the negative electrode away from the lithium ion battery cell gradually decrease. When the temperature is low, the rate of forming the SEI film is slow, and it is easier to form a dense SEI film; when the temperature is high, the rate of forming the SEI film is fast, and it is easier to form a loose and porous SEI film. The temperature of each formation gradually increases, which can make the density of the m layers of SEI film stacked in sequence from the negative electrode close to the lithium ion battery cell to the negative electrode away from the lithium ion battery cell gradually decrease. The temperature of each formation is less than or equal to 70°C, which can avoid the structure of the SEI film being too loose and having poor structural stability. Density is used to characterize the density of the SEI film structure. From the negative electrode close to the lithium-ion battery cell to the negative electrode far away from the lithium-ion battery cell, the density of the m layers of SEI films stacked in sequence gradually decreases. The density of the SEI film close to the negative electrode of the lithium-ion battery cell is high, and the density of the SEI film far away from the negative electrode of the lithium-ion battery cell is low. The high-density SEI film can separate the negative electrode from the dense SEI film, play a blocking role, and prevent the low-density SEI film from directly contacting the negative electrode. In the later charging and discharging process, when the negative electrode of the lithium-ion battery cell expands and contracts, the structure of the SEI film is damaged, and the electrolyte directly contacts the negative electrode of the lithium-ion battery cell, reacts with the negative electrode, and affects the cycle performance of the lithium-ion battery cell. The SEI membrane structure close to the negative electrode of the lithium-ion battery cell in the composite SEI membrane is stable, and can also prevent the SEI membrane at the negative electrode far away from the lithium-ion battery cell from directly contacting the negative electrode material, thereby enhancing the overall structural stability of the composite SEI membrane. At the same time, the SEI membrane structure at the negative electrode far away from the lithium-ion battery cell is loose and porous, with low impedance, which is convenient for the transmission of lithium ions, thereby improving the cycle performance of the lithium-ion battery cell.

[0011] Optionally, the organic additive includes at least one of vinylene carbonate, propylene sulfite, vinyl sulfate, vinylene carbonate, and fluoroethylene carbonate;

[0012] The inorganic additive includes at least one of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonate)imide.

[0013] Optionally, the first total mass of the electrolyte used from the first injection to the nth injection accounts for 60% to 90% of the second total mass of the electrolyte used from the first injection to the mth injection;

[0014] The third total mass of the electrolyte used in the n+1th injection to the mth injection accounts for 10% to 40% of the second total mass.

[0015] Optionally, after the nth formation, the state of charge of the lithium-ion battery cell is 30% to 40%;

[0016] After the m-th formation, the state of charge of the lithium-ion battery cell is 70% to 100%.

[0017] Optionally, from the first injection to the nth injection, the mass fraction of the organic additive used in one injection in the electrolyte used in the same injection is 5% to 10%;

[0018] From the n+1th injection to the mth injection, the mass fraction of the inorganic additive used in one injection in the electrolyte used in the same injection is 8% to 15%.

[0019] Optionally, in the first formation, the constant current charging of the lithium ion battery cell comprises:

[0020] First, a first constant current charge is performed at a current rate of 0.01 to 0.03, and then a second constant current charge is performed at a current rate of 0.05 to 0.2.

[0021] Optionally, in the m-th formation, the constant current charging of the lithium-ion battery cell comprises:

[0022] First, the third constant current charging is performed at a current rate of 0.2 times to 0.5 times, and then the fourth constant current charging is performed at a current rate of 0.5 times to 1 times.

[0023] Optionally, the temperature of the first formation is 15° C. to 30° C.;

[0024] The temperature of the m-th formation is 40° C. to 70° C.

[0025] A second aspect of the present invention provides a lithium-ion battery cell, comprising: a negative electrode, and a composite SEI film located on the negative electrode, wherein the negative electrode is the negative electrode mentioned in the method for preparing the SEI film described in the first aspect, and the composite SEI film is prepared using the method for preparing the SEI film described in the first aspect.

[0026] A third aspect of the present invention provides a lithium ion battery, comprising the lithium ion battery cell as described in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0028] Figure 1 A flow chart showing the steps of a method for preparing a SEI film in an embodiment of the present invention is shown;

[0029] Figure 2 A schematic structural diagram of a composite SEI film in an embodiment of the present invention is shown;

[0030] Figure 3 A cycle performance test graph is shown.

[0031] Description of reference numerals:

[0032] 11- graphite, 12- first SEI film, 13- second SEI film. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention provides a method for preparing a SEI film. Figure 1 , Figure 1 A flow chart showing the steps of a method for preparing a SEI film in an embodiment of the present invention is shown, and the method comprises:

[0035] Step 101, performing m injections and m formations on the lithium ion battery cell, performing the formation once after each injection, so as to form a composite SEI film on the negative electrode of the lithium ion battery cell; each injection includes: injecting electrolyte into the lithium ion battery cell; each formation includes: performing constant current charging on the lithium ion battery cell, so as to form a layer of SEI film on the negative electrode of the lithium ion battery cell; the composite SEI film is formed by stacking m layers of SEI films formed by each SEI film formed by the formation; m is greater than or equal to 2, and m is a positive integer; from the first injection to the nth injection, The electrolyte used contains an organic additive; from the n+1th injection to the mth injection, the electrolyte used contains an inorganic additive; n is greater than or equal to 1, and n is less than m; n is a positive integer; from the first formation to the mth formation, the current of the constant current charging of each formation gradually increases; from the first formation to the mth formation, the temperature of each formation gradually increases; the temperature of each formation is less than or equal to 70°C; from the negative electrode close to the lithium ion battery cell to the negative electrode away from the lithium ion battery cell, the density of the m layers of SEI films stacked in sequence gradually decreases.

[0036] m is greater than or equal to 2, and m is a positive integer. For example, m can be 2, 3, 4, 5, 6, or 7. The composite SEI film is formed by sequentially stacking m layers of SEI films formed by each layer of SEI film formed by each chemical formation. The structures or components of the SEI films of different layers can be adjusted separately, so as to obtain a composite SEI film with better performance.

[0037] Organic additives are conducive to the preparation of SEI membranes with good flexibility, ensuring that the main component of the SEI membrane is organic. In the later charging and discharging process, the negative electrode of the lithium-ion battery will expand and shrink. The SEI membrane has good flexibility and is not easy to crack. It has good structural stability and can prevent the electrolyte from reacting with the negative electrode. It consumes no or very little electrolyte and enhances the cycle performance of the lithium-ion battery. Inorganic additives are conducive to the preparation of loose and porous SEI membranes, forming SEI membranes whose main components are inorganic components. The SEI membrane is loose and porous, and the impedance of the SEI membrane is small, which is conducive to the transmission of lithium ions in the SEI membrane and will also improve the rate performance of the lithium-ion battery. n is greater than or equal to 1, and n is less than m; n is a positive integer; for example, when m is 4, n can be 1, 2, or 3. When n is 2, from the first injection to the second injection, the electrolyte used contains organic additives; from the third injection to the fourth injection, the electrolyte used contains inorganic additives. When m is 2, n can be 1, and in the first injection, the electrolyte used contains organic additives; in the second injection, the electrolyte used contains inorganic additives.

[0038] When the current is small, the rate of SEI film formation is slow, and it is easier to form a dense SEI film; when the current is large, the rate of SEI film formation is fast, and it is easier to form a loose and porous SEI film. The current of each constant current charge gradually increases, which can make the density of the m layers of SEI film stacked from the negative electrode close to the lithium-ion battery cell to the negative electrode away from the lithium-ion battery cell gradually decrease. When the temperature is low, the rate of SEI film formation is slow, and it is easier to form a dense SEI film; when the temperature is high, the rate of SEI film formation is fast, and it is easier to form a loose and porous SEI film. The temperature of each formation gradually increases, which can make the density of the m layers of SEI film stacked from the negative electrode close to the lithium-ion battery cell to the negative electrode away from the lithium-ion battery cell gradually decrease. The temperature of each formation is less than or equal to 70°C (degrees Celsius). For example, the temperature of each formation can be 20°C, 30°C, 35°C, 50°C, 60°C, or 70°C. The temperature of each formation is less than or equal to 70°C, which can prevent the structure of the SEI film from being too loose and having poor structural stability.

[0039] The negative electrode of the lithium-ion battery cell can be graphite 11. Density refers to the ratio of mass to volume of a substance at a certain temperature and pressure. From the negative electrode close to the lithium-ion battery cell to the negative electrode far away from the lithium-ion battery cell, the density of the m-layer SEI film stacked in sequence gradually decreases. Specifically, it means that at the same temperature and pressure, from the negative electrode close to the lithium-ion battery cell to the negative electrode far away from the lithium-ion battery cell, the mass to volume ratio of the m-layer SEI film stacked in sequence gradually decreases. The density of the SEI film close to the negative electrode of the lithium-ion battery cell is high, and the density of the SEI film far away from the negative electrode of the lithium-ion battery cell is low. The high-density SEI film can separate the negative electrode from the dense SEI film, play a blocking role, and prevent the low-density SEI film from directly contacting the negative electrode. In the later charging and discharging process, when the negative electrode of the lithium-ion battery cell expands and contracts, the structure of the SEI film is damaged, and the electrolyte directly contacts the negative electrode of the lithium-ion battery cell and reacts with the negative electrode, affecting the cycle performance of the lithium-ion battery cell.

[0040] The inventors found that in the prior art, when preparing the SEI film, in order to ensure the structural stability of the SEI film, a dense SEI film is usually prepared. However, using this prior art, the SEI film is dense and has a large impedance, which is not conducive to the transmission of lithium ions, resulting in poor cycle performance of lithium-ion batteries.

[0041] In view of the above problems, the inventors creatively form a multilayer SEI film on the negative electrode of the lithium-ion battery cell. In the embodiment of the present invention, the lithium-ion battery cell is injected and formed m times, and each injection is followed by a formation to form a composite SEI film on the negative electrode of the lithium-ion battery cell; each injection includes: injecting electrolyte into the lithium-ion battery cell; each formation includes: constant current charging the lithium-ion battery cell to form a layer of SEI film on the negative electrode of the lithium-ion battery cell; the composite SEI film is formed by stacking m layers of SEI film in sequence, each layer of SEI film formed by each formation; the structure or composition of the SEI film of different layers can be adjusted separately, so as to obtain a composite SEI film with better performance. From the first injection to the nth injection, the electrolyte used contains organic additives; from the n+1th injection to the mth injection, the electrolyte used contains inorganic additives; organic additives are conducive to the preparation of SEI membranes with good flexibility. In the later charging and discharging process, the negative electrode of the lithium-ion battery will expand and shrink. The SEI membrane has good flexibility, is not easy to crack, and has good structural stability; inorganic additives are conducive to the preparation of loose and porous SEI membranes. The SEI membrane is loose and porous, and the impedance of the SEI membrane is small, which is conducive to the transmission of lithium ions in the SEI membrane, and also improves the rate performance of the lithium-ion battery. When the current is small, the rate of forming the SEI membrane is slow, and it is easier to form a dense SEI membrane; when the current is large, the rate of forming the SEI membrane is fast, and it is easier to form a loose and porous SEI membrane. The current of each constant current charge gradually increases, which can make the density of the m layers of SEI membranes stacked in sequence from the negative electrode close to the lithium-ion battery to the negative electrode away from the lithium-ion battery gradually decrease. When the temperature is low, the rate of SEI film formation is slow, and it is easier to form a dense SEI film; when the temperature is high, the rate of SEI film formation is fast, and it is easier to form a loose and porous SEI film. The temperature of each formation gradually increases, which can make the density of the m layers of SEI film stacked in sequence from the negative electrode close to the lithium-ion battery cell to the negative electrode away from the lithium-ion battery cell gradually decrease. The temperature of each formation is less than or equal to 70°C, which can avoid the structure of the SEI film being too loose and having poor structural stability. Density is used to characterize the density of the SEI film structure. From the negative electrode close to the lithium-ion battery cell to the negative electrode away from the lithium-ion battery cell, the density of the m layers of SEI film stacked in sequence gradually decreases. The density of the SEI film close to the negative electrode of the lithium-ion battery cell is high, and the density of the SEI film far away from the negative electrode of the lithium-ion battery cell is low. The high-density SEI film can separate the negative electrode from the dense SEI film, play a barrier role, and prevent the low-density SEI film from directly contacting the negative electrode. In the later charging and discharging process, when the negative electrode of the lithium-ion battery cell expands and contracts, the structure of the SEI film is destroyed, and the electrolyte directly contacts the negative electrode of the lithium-ion battery cell, reacts with the negative electrode, and affects the cycle performance of the lithium-ion battery cell.The SEI membrane structure close to the negative electrode of the lithium-ion battery cell in the composite SEI membrane is stable, and can also prevent the SEI membrane at the negative electrode far away from the lithium-ion battery cell from directly contacting the negative electrode material, thereby enhancing the overall structural stability of the composite SEI membrane. At the same time, the SEI membrane structure at the negative electrode far away from the lithium-ion battery cell is loose and porous, with low impedance, which is convenient for the transmission of lithium ions, thereby improving the cycle performance of the lithium-ion battery cell.

[0042] In the embodiment of the present invention, the density of the SEI film can also be tested by atomic force microscopy. The structure of the SEI film can be visually seen through atomic force microscopy imaging, and the parameter etching force can be used to characterize the density of the SEI film.

[0043] Optionally, the organic additive includes at least one of vinylene carbonate, propylene sulfite, vinyl sulfate, vinylene carbonate, and fluoroethylene carbonate; the inorganic additive includes at least one of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonate)imide.

[0044] When the organic additive includes at least one of vinyl carbonate (VC), propylene sulfite (PS), vinyl sulfate (DTD), vinyl carbonate (VEC), and fluoroethylene carbonate (FEC), the SEI film formed has better flexibility and better structural stability, and these additives are low in price and low in toxicity; when the inorganic additive includes at least one of lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl) imide (LiFSI), and lithium bis(trifluoromethylsulfonate) imide (LiTFSI), it is easier to form a loose and porous SEI film structure, and these additives are low in price and low in toxicity. Optionally, the organic additive also includes other ester electrolyte additives.

[0045] The electrolyte also includes a solvent. Optionally, the solvent in the electrolyte used for the first injection to the mth injection includes at least two of diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethylene carbonate (EC), vinylene carbonate (VC), and vinylene carbonate (VEC). In the case of including at least two, the SEI film formed can be prevented from having a single component and unstable performance. Optionally, from the 1st injection to the nth injection, the mass fraction of the solvent in the electrolyte used for each injection is 74% to 85%, for example, the mass fraction of the solvent in the electrolyte used for each injection may be 74%, or 75%, or 77%, or 80%, or 82%, or 85%; from the n+1th injection to the mth injection, the mass fraction of the solvent in the electrolyte used for each injection is 69% to 82%, for example, the mass fraction of the solvent in the electrolyte used for each injection may be 69%, or 70%, or 72%, or 75%, or 80%, or 82%.

[0046] The electrolyte also includes a lithium salt. Optionally, the lithium salt in the electrolyte used for the first injection to the mth injection is lithium hexafluorophosphate (LiPF6). Lithium hexafluorophosphate is cheap and has low toxicity. Optionally, in the first injection to the mth injection, the mass fraction of the lithium salt in the electrolyte used for each injection is 10% to 16%, for example, the mass fraction of the lithium salt in the electrolyte used for each injection is 10%, or 11%, or 12%, or 13%, or 14%, or 16%.

[0047] Optionally, the first total mass of the electrolyte used in the first injection to the nth injection accounts for 60% to 90% of the second total mass of the electrolyte used in the first injection to the mth injection; the third total mass of the electrolyte used in the n+1th injection to the mth injection accounts for 10% to 40% of the second total mass. For example, the first total mass of the electrolyte used in the first injection to the nth injection accounts for 60%, or 65%, or 70%, or 75%, or 80%, or 90% of the second total mass of the electrolyte used in the first injection to the mth injection; the third total mass of the electrolyte used in the n+1th injection to the mth injection accounts for 10%, or 15%, or 20%, or 25%, or 30%, or 40% of the second total mass. For example, when m is 2 and n is 1, the first total mass of the electrolyte used in the first injection accounts for 60% of the second total mass of the electrolyte used from the first injection to the second injection, and the third total mass of the electrolyte used in the second injection accounts for 40% of the second total mass. For example, when m is 3 and n is 2, the first total mass of the electrolyte used in the first injection to the second injection accounts for 70% of the second total mass of the electrolyte used from the first injection to the third injection, and the third total mass of the electrolyte used in the third injection accounts for 30% of the second total mass.

[0048] From the first injection to the nth injection, the electrolyte used contains organic additives, and the SEI film formed each time has good flexibility. From the n+1th injection to the mth injection, the electrolyte used contains inorganic additives, and the SEI film formed each time is loose. The first total mass of the electrolyte used from the first injection to the nth injection accounts for 60% to 90% of the second total mass of the electrolyte used from the first injection to the mth injection. The third total mass of the electrolyte used from the n+1th injection to the mth injection accounts for 60% to 90% of the second total mass of the electrolyte used The total mass accounts for 10% to 40% of the second total mass, which can ensure that a complete organic SEI film can be formed after the first injection to the nth injection and the nth formation. The mass fraction of the electrolyte used in the first injection to the nth injection is higher than that of the electrolyte used in the n+1th injection to the mth injection. Even if at least the electrolyte used in the first injection is also used to fill the gap between the diaphragm, the positive electrode and the negative electrode of the lithium-ion battery cell, a complete organic SEI film can be formed.

[0049] Optionally, after the nth formation, the state of charge of the lithium-ion battery is 30% to 40%; after the mth formation, the state of charge of the lithium-ion battery is 70% to 100%. For example, after the nth formation, the state of charge of the lithium-ion battery can be 30%, or 32%, or 34%, or 36%, or 38%, or 40%; after the mth formation, the state of charge of the lithium-ion battery can be 70%, or 75%, or 80%, or 85%, or 90%, or 100%.

[0050] From the first formation to the mth formation, the current of the constant current charging of each formation gradually increases, that is, the current from the first formation to the nth formation is small. After the nth formation, the state of charge (SOC) of the lithium ion battery cell is 30% to 40%, indicating that the charging time of the lithium ion battery cell is relatively long, which can ensure that the formed SEI film structure can completely cover the negative electrode of the lithium ion battery cell, thereby better preventing the SEI film away from the negative electrode of the lithium ion battery cell from directly contacting the negative electrode material, and at the same time, avoiding the state of charge of the lithium ion battery cell from exceeding 40%. When the charging time of the lithium ion battery cell is too long, the thickness of the dense SEI film is too thick and the thickness of the loose SEI film is too thin, which is not conducive to the transmission of lithium ions, and the impedance is large, which affects the cycle performance of the lithium ion battery cell. After the mth formation, the state of charge of the lithium-ion battery cell is 70% to 100%, which can ensure that the SEI film structure is fully formed and completely covers the negative electrode material, and can remain stable during the subsequent charging and discharging process to ensure the normal use of the lithium-ion battery cell. Optionally, the range of the state of charge of the lithium-ion battery cell after each formation can be determined according to the material system of the lithium-ion battery cell.

[0051] Optionally, from the 1st injection to the nth injection, the mass fraction of the organic additive used in one injection in the electrolyte used in the same injection is 5% to 10%; from the n+1th injection to the mth injection, the mass fraction of the inorganic additive used in one injection in the electrolyte used in the same injection is 8% to 15%.

[0052] For example, in the first injection to the nth injection, the mass fraction of the organic additive used in one injection in the electrolyte used in the same injection can be 5%, or 6%, or 7%, or 8%, or 9%, or 10%, for example, the mass fraction of the organic additive used in the first injection in the electrolyte used in the first injection is 5%; in the n+1th injection to the mth injection, the mass fraction of the inorganic additive used in one injection in the electrolyte used in the same injection can be 8%, or 9%, or 10%, or 12%, or 13%, or 15%, for example, m is 3, and the mass fraction of the inorganic additive used in the third injection in the electrolyte used for the third injection is 15%.

[0053] From the first injection to the nth injection, the mass fraction of the organic additive used in the first injection in the electrolyte used in the same injection is 5% to 10%, which can ensure that the organic additive has the effect of improving the flexibility of the SEI film; from the n+1th injection to the mth injection, the mass fraction of the inorganic additive used in the first injection in the electrolyte used in the same injection is 8% to 15%, which can ensure that the inorganic additive has the effect of making the structure of the SEI film loose and porous; at the same time, the mass fractions of organic additives and inorganic additives are both low, which can ensure that the mass fractions of lithium salts and solvents in the electrolyte containing organic additives and the electrolyte containing inorganic additives are both high, avoiding the low mass fraction of lithium salts, affecting the transmission performance of lithium ions, or avoiding the low mass fraction of solvents, affecting the physical properties of the electrolyte, such as the viscosity and low-temperature crystallinity of the electrolyte. In addition, the mass fractions of organic additives and inorganic additives are both low, which can reduce the amount of additives used. The price of additives is high, and reducing the amount of additives used can reduce costs.

[0054] Optionally, in the first formation, constant current charging of the lithium-ion battery cell includes: firstly performing a first constant current charging at a current rate of 0.01 to 0.03, and then performing a second constant current charging at a current rate of 0.05 to 0.2. For example, the current for the first constant current charging may be 0.01C (rate), or 0.015C, or 0.02C, or 0.025C, or 0.028C, or 0.03C; the current for the second constant current charging may be 0.05C, or 0.08C, or 0.1C, or 0.13C, or 0.15C, or 0.2C. Charge and discharge rate = charge and discharge current / rated capacity, the unit of charge and discharge rate is C, the unit of charge and discharge current is A (ampere), and the unit of rated capacity is Ah (ampere-hour). For example, when the capacity of the lithium-ion battery is 20Ah, the current for the first constant current charging can be 0.2A to 0.6A, and the current for the second constant current charging can be 1A to 4A. The charge and discharge rate of the first constant current charging = (0.2A to 0.6A) / 20Ah = 0.01C to 0.03C, and the charge and discharge rate of the second constant current charging = (1A to 4A) / 20Ah = 0.05C to 0.2C.

[0055] The current of the first constant current charging is smaller than that of the second constant current charging, which can avoid the charging current exceeding the carrying capacity range of the lithium-ion battery cell under the corresponding state of charge. Moreover, when performing two constant current charging, the current of the second constant current charging is larger than that of the first constant current charging. The time of the second constant current charging can be shorter than that of the first constant current charging, which can save charging time. In addition, the currents of the two constant current charging are both small, which is conducive to the formation of a dense SEI film.

[0056] Optionally, the time for the first constant current charging is 180min (minutes) to 600min, for example, the time for the first constant current charging can be 180min, or 250min, or 360min, or 420min, or 540min, or 600min, and the time for the second constant current charging is 75min to 300min, for example, the time for the second constant current charging can be 75min, or 110min, or 140min, or 200min, or 250min, or 300min. The specific time for constant current charging can be calculated according to the current for constant current charging and the state of charge of the lithium ion battery to be achieved. The time for the first constant current charging and the second constant current charging is longer, which can ensure that the thickness of the formed SEI film is thicker and the structural stability is better.

[0057] Optionally, in the mth formation, constant current charging of the lithium-ion battery cell includes: first performing a third constant current charging at a current rate of 0.2 to 0.5, and then performing a fourth constant current charging at a current rate of 0.5 to 1. For example, the current for the third constant current charging may be 0.2C, or 0.25C, or 0.3C, or 0.35C, or 0.4C, or 0.5C; the current for the fourth constant current charging may be 0.5C, or 0.6C, or 0.7C, or 0.8C, or 0.9C, or 1C.

[0058] The current of the third constant current charging is smaller than that of the fourth constant current charging, which can avoid the charging current exceeding the carrying capacity range of the lithium-ion battery cell under the corresponding state of charge. Moreover, in the case of two constant current charging, the current of the fourth constant current charging is larger than that of the third constant current charging. The time of the fourth constant current charging can be shorter than that of the third constant current charging, which can save charging time. In addition, the currents of the two constant current charging are both large, which is conducive to the formation of a loose and porous SEI film.

[0059] Optionally, the time for the third constant current charging is 15min to 30min, for example, the time for the third constant current charging can be 15min, or 18min, or 20min, or 22min, or 25min, or 30min, and the time for the fourth constant current charging is 15min to 30min, for example, the time for the fourth constant current charging can be 15min, or 18min, or 20min, or 22min, or 25min, or 30min. The specific time for constant current charging can be calculated according to the current for constant current charging and the state of charge of the lithium ion battery to be achieved.

[0060] Optionally, the temperature of the first formation is 15°C to 30°C; the temperature of the m-th formation is 40°C to 70°C. For example, the temperature of the first formation may be 15°C, or 22°C, or 25°C, or 26°C, or 28°C, or 30°C; the temperature of the m-th formation may be 40°C, or 45°C, or 48°C, or 50°C, or 60°C, or 70°C. The temperature of the first formation is 15°C to 30°C, and the temperature of the first formation is relatively low, which is conducive to the formation of a denser SEI film; the temperature of the m-th formation is 40°C to 70°C, and the temperature of the m-th formation is relatively high, which is conducive to the formation of a loose and porous SEI film.

[0061] Optionally, the battery cell includes an aluminum shell battery cell or a cylindrical battery cell. When the formation is performed at least twice, the aluminum shell battery cell or the cylindrical battery cell is made of a harder material and is easy to operate.

[0062] Optionally, after each injection and before each formation, the method further includes: placing the lithium-ion battery cell in a vacuum state for a preset time at a preset temperature.

[0063] The embodiment of the present invention also provides a lithium ion battery cell, comprising: a negative electrode, and a composite SEI film located on the negative electrode, wherein the negative electrode is the negative electrode mentioned in the preparation method of the above-mentioned SEI film, and the composite SEI film is prepared by the preparation method of the above-mentioned SEI film. The composite SEI film is prepared by the preparation method of the above-mentioned SEI film, and the density of the m layers of SEI films stacked in sequence gradually decreases from the negative electrode close to the lithium ion battery cell to the negative electrode far away from the lithium ion battery cell. The SEI film structure of the composite SEI film close to the negative electrode of the lithium ion battery cell is stable, and it can also prevent the SEI film of the negative electrode far away from the lithium ion battery cell from directly contacting the negative electrode material, thereby enhancing the overall structural stability of the composite SEI film. At the same time, the SEI film structure of the negative electrode far away from the lithium ion battery cell is loose and porous, with low impedance, which is convenient for the transmission of lithium ions, thereby improving the cycle performance of the lithium ion battery cell.

[0064] The embodiment of the present invention further provides a lithium-ion battery, comprising the above-mentioned lithium-ion battery cell. The SEI film of the above-mentioned lithium-ion battery cell is prepared by the above-mentioned SEI film preparation method, and the cycle performance of the lithium-ion battery cell is improved, thereby improving the cycle performance of the lithium-ion battery. Optionally, the lithium-ion battery includes an aluminum shell lithium-ion battery or a cylindrical lithium-ion battery.

[0065] The present invention is further explained below in conjunction with specific embodiments.

[0066] An experimental group and a comparative group were set up. Both the experimental group and the comparative group were lithium iron phosphate system cells with a rated capacity of 20Ah and a negative electrode of graphite 11. The specific parameters of the electrolyte used in the experimental group and the comparative group are shown in Table 1. The values ​​in Table 1 represent the mass fraction of each component in the electrolyte, in %. The mass fraction of each component of electrolyte 3 is converted according to the mass fraction of each component of electrolyte 1 and electrolyte 2, and the mass ratio of electrolyte 1 and electrolyte 2, so that the comparison between the experimental group and the comparative group is more rigorous.

[0067] Table 1 Electrolyte composition

[0068]

[0069] The experimental group prepared the SEI film using a method for preparing the SEI film in an embodiment of the present invention, and the specific steps are as follows:

[0070] (1) Performing the first electrolyte injection and the first formation on the lithium ion battery cell: injecting electrolyte 1 into the lithium ion battery cell, the mass of electrolyte 1 accounts for 80% of the total mass of electrolyte 1 and electrolyte 2; placing the lithium ion battery cell in a vacuum state for 8 hours at 45° C.; performing the steps in Table 2 in sequence, the temperature of the first formation is 25° C., forming a first SEI film 12, referring to Figure 2 , Figure 2 A schematic diagram of the structure of a composite SEI film in an embodiment of the present invention is shown, in which a first organic SEI film 12 with good flexibility covers the surface of graphite 11, and a second inorganic SEI film 13 with a loose porous structure is located on the side of the first SEI film 12 away from the graphite 11;

[0071] Table 2 Specific process of the first formation

[0072]

[0073] (2) Performing a second injection and a second formation on the lithium-ion battery cell: injecting electrolyte 2 into the lithium-ion battery cell, wherein the mass of electrolyte 2 accounts for 20% of the total mass of electrolyte 1 and electrolyte 2; placing the lithium-ion battery cell in a vacuum state at 45°C for 8 hours; and performing the steps in Table 3 in sequence, wherein the temperature of the second formation is 45°C, forming a second SEI film 13, and obtaining a composite SEI film formed by sequentially stacking the first SEI film 12 and the second SEI film 13.

[0074] Table 3 Specific process of the second formation

[0075]

[0076] The control group prepared the SEI film using a SEI film preparation method in the prior art, and the specific steps are as follows:

[0077] (1) Performing the first injection and the first formation of the lithium-ion battery cell: injecting electrolyte 3 into the lithium-ion battery cell, where electrolyte 3 is the entire electrolyte used in the control group; placing the lithium-ion battery cell in a vacuum at 45° C. for 8 h; and performing the steps in Table 2 in sequence, with the temperature of the first formation being 25° C.;

[0078] (2) Performing the second formation of the lithium-ion battery cell: Performing the steps in Table 3 in sequence, with the temperature of the second formation being 45° C.

[0079] After the above steps are completed, the lithium-ion batteries of the experimental group and the comparative group are subjected to degassing and capacity separation steps under the same conditions, and then the cycle performance test is carried out under the same conditions (the test temperature is room temperature). The test results are shown in Table 4 and Figure 3 As shown, Figure 3 The cycle performance test curve is shown, and the capacity retention rate of the lithium-ion battery cell decreases with the increase of the cycle number.

[0080] Table 4 Cyclic performance test results

[0081] Group Cycle number Capacity retention rate Experimental Group 2212 81.12% Comparison group 1182 76.22%

[0082] Depend on Figure 3 As shown in Table 4, under the same battery system conditions, the experimental group has more cycles than the control group, the capacity retention rate of the experimental group is higher than that of the control group, and the experimental group has better cycle performance than the control group. The experimental group adopts a method for preparing a SEI film in an embodiment of the present invention. The first formation adopts low temperature and low current conditions, so that the first SEI film 12 formed on the surface of graphite 11 is dense, and the electrolyte of the first injection contains organic additives, so that the main component of the first SEI film 12 is organic components, with good flexibility and good structural stability; the second formation adopts high temperature and high current conditions, and the electrolyte of the second injection contains inorganic additives, so that the second SEI film 13 is loose and porous, and the main component is inorganic components, with low impedance, which is conducive to the transmission of lithium ions. The control group forms a loose and porous organic and inorganic doped SEI film. Compared with the control group, the first organic SEI film 12 covering the surface of the graphite 11 in the experimental group has good structural stability and is not easily damaged during the later cycle process, while the second inorganic SEI film 13 is loose and porous and has better lithium ion transmission performance. Therefore, the structure of the composite SEI film obtained in the experimental group enables the lithium ion battery to have better cycle performance.

[0083] It should be noted that the aforementioned preparation method of the SEI film, the lithium-ion battery cell, and the lithium-ion battery can be mutually referenced in their related parts, and can achieve the same or similar effects.

[0084] It should be noted that, for the method embodiments, for the sake of simplicity of description, they are all expressed as a series of action combinations, but those skilled in the art should be aware that the embodiments of the present application are not limited by the described order of actions, because according to the embodiments of the present application, certain steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also be aware that the embodiments described in the specification are all preferred embodiments, and the actions involved are not necessarily required by the embodiments of the present application.

[0085] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0086] It should be noted that, in this document, the terms "first", "second", etc. in the specification and claims are used to distinguish similar objects, rather than to describe a specific order or sequence. Moreover, the objects distinguished by "first", "second", etc. are usually of the same type, and the number of objects is not limited. For example, the second object can be one.

[0087] Through the description of the above implementation methods, those skilled in the art can clearly understand that the above-mentioned embodiment methods can be implemented by means of software plus a necessary general hardware platform, and of course by hardware, but in many cases the former is a better implementation method. Based on such an understanding, the technical solution of the present invention, or the part that contributes to the prior art, can be embodied in the form of a software product, which is stored in a storage medium (such as ROM / RAM, a magnetic disk, or an optical disk), and includes a number of instructions for enabling a terminal (which can be a mobile phone, a computer, a server, an air conditioner, or a network device, etc.) to execute the methods described in each embodiment of the present invention.

[0088] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a SEI film, characterized in that: include: Performing m injections and m formations on the lithium-ion battery cell, performing the formation once after each injection, so as to form a composite SEI film on the negative electrode of the lithium-ion battery cell; Each injection includes: injecting electrolyte into the lithium ion battery cell; each formation includes: charging the lithium ion battery cell with a constant current to form a SEI film on the negative electrode of the lithium ion battery cell; the composite SEI film is formed by stacking m SEI films in sequence, each SEI film formed by each formation; m is greater than or equal to 2, and m is a positive integer; From the first injection to the nth injection, the electrolyte used contains an organic additive; from the n+1th injection to the mth injection, the electrolyte used contains an inorganic additive; n is greater than or equal to 1, and n is less than m; n is a positive integer; From the first formation to the mth formation, the current of the constant current charging of each formation gradually increases; from the first formation to the mth formation, the temperature of each formation gradually increases; the temperature of each formation is less than or equal to 70° C.; The density of the m layers of SEI films stacked sequentially decreases gradually from the negative electrode close to the lithium ion battery cell to the negative electrode far away from the lithium ion battery cell.

2. The method for preparing the SEI film according to claim 1, characterized in that: The organic additive includes at least one of vinylene carbonate, propylene sulfite, vinyl sulfate, vinylene carbonate, and fluoroethylene carbonate; The inorganic additive includes at least one of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonate)imide.

3. The method for preparing the SEI film according to claim 1, characterized in that: The first total mass of the electrolyte used in the first injection to the nth injection accounts for 60% to 90% of the second total mass of the electrolyte used in the first injection to the mth injection; The third total mass of the electrolyte used in the n+1th injection to the mth injection accounts for 10% to 40% of the second total mass.

4. The method for preparing the SEI film according to claim 1, characterized in that: After the nth formation, the state of charge of the lithium-ion battery cell is 30% to 40%; After the m-th formation, the state of charge of the lithium-ion battery cell is 70% to 100%.

5. The method for preparing the SEI film according to claim 1, characterized in that: From the first injection to the nth injection, the mass fraction of the organic additive used in one injection in the electrolyte used in the same injection is 5% to 10%; From the n+1th injection to the mth injection, the mass fraction of the inorganic additive used in one injection in the electrolyte used in the same injection is 8% to 15%.

6. The method for preparing a SEI film according to any one of claims 1 to 5, characterized in that: In the first formation, the constant current charging of the lithium ion battery cell comprises: First, a first constant current charge is performed at a current rate of 0.01 to 0.03, and then a second constant current charge is performed at a current rate of 0.05 to 0.

2.

7. The method for preparing a SEI film according to any one of claims 1 to 5, characterized in that: In the mth formation, the constant current charging of the lithium ion battery cell comprises: First, the third constant current charging is performed at a current rate of 0.2 times to 0.5 times, and then the fourth constant current charging is performed at a current rate of 0.5 times to 1 times.

8. The method for preparing a SEI film according to any one of claims 1 to 5, characterized in that: The temperature of the first formation is 15°C to 30°C; The temperature of the m-th formation is 40° C. to 70° C.

9. A lithium-ion battery cell, characterized in that: include: A negative electrode, and a composite SEI film located on the negative electrode, wherein the negative electrode is the negative electrode mentioned in the method for preparing the SEI film as described in any one of claims 1 to 8, and the composite SEI film is prepared by the method for preparing the SEI film as described in any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: Comprising the lithium-ion battery cell as claimed in claim 9.